Odpowiedź :
[tex](2\frac{2}{3})^{1\frac{1}{2}}:(\frac{2}{3})^{1\frac{1}{2}} = (\frac{8}{3})^{\frac{3}{2}}:(\frac{2}{3})^{\frac{3}{2}} = (\frac{8}{3}\cdot\frac{3}{2})^{\frac{3}{2}} = 4^{\frac{3}{2}} = (2^{2})^{\frac{3}{2}} = 2^{3} = 8\\\\((\frac{4}{9})^{\frac{3}{4}})^{-\frac{2}{3}} = (\frac{4}{9})^{\frac{3}{4}\cdot(-\frac{2}{3})} = (\frac{4}{9})^{-\frac{1}{2}} = (\frac{9}{4})^{\frac{1}{2}} = ((\frac{3}{2})^{2})^\frac{1}{2}} = (\frac{3}{2})^{1}=\frac{3}{2} = 1\frac{1}{2}[/tex]
Odpowiedź:
(2 2/3) ³/²: (2/3)³/²= ( 8/3*3/2)³/²= 4³/²= ( 2²)³/²=2³=8
[( 4/9) ³/⁴] ⁻²/³= (4/9)⁻¹/²= [(2/3)²]⁻¹/²= (2/3)⁻¹=3/2=1 1/2
Szczegółowe wyjaśnienie: